2018
DOI: 10.1111/vox.12740
|View full text |Cite
|
Sign up to set email alerts
|

Recipient sepsis caused by Lactococcus garvieae contamination of platelets from a donor with colon cancer

Abstract: Lactococcus garvieae is a well‐known fish pathogen that has low virulence in humans and is rarely isolated from the blood cultures of endocarditis patients. We describe herein the first reported case of transfusion‐transmitted L. garvieae sepsis caused by a contaminated platelet concentrate from a donor who consumed raw octopus before blood donation. Retrospective examination of the laboratory results of the index donor revealed that his haemoglobin levels had been steadily decreasing, which led to the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In view of this and other reports that described sepsis associated with L. garvieae infection [ 11 , 13 , 50 , 51 ], the knowledge of virulence factors and resistance mechanisms associated with the Lactococcus genera and L. garvieae species is detrimental.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In view of this and other reports that described sepsis associated with L. garvieae infection [ 11 , 13 , 50 , 51 ], the knowledge of virulence factors and resistance mechanisms associated with the Lactococcus genera and L. garvieae species is detrimental.…”
Section: Discussionmentioning
confidence: 91%
“…In 2018, the first case of transfusion-transmitted L. garvieae resulting from a platelet transfusion in an adult hospitalized individual was described [ 13 ]. Here, we describe a cluster of transmission, with three cases of sepsis in onco-hematologic pediatric patients, derived by transfusion-transmitted L. garvieae from platelet concentrates (PCs) of the same donor.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, a septic transfusion reaction is identified when investigations following the transfusion reaction identify the same bacterial strain in the PC and the donorʼs blood . In some scenarios, bacteria may contaminate units from a donor with asymptomatic bacteremia . After release of the unit to the transfusion service, small pinhole leaks or other bag leaks may also cause contamination of the unit …”
Section: Discussionmentioning
confidence: 99%
“…The first case of transfusion-transmitted Lactococcus garvieae sepsis caused by a contaminated PC from a donor who consumed raw octopus before blood donation was reported [41]. Retrospective examination of the laboratory results of the index donor revealed that his haemoglobin levels had been steadily decreasing, which led to the detection of a latent colon cancer.…”
Section: Detection Systemsmentioning
confidence: 99%